A fusion protein of vimentin with Fc fragment inhibits Japanese encephalitis virus replication - Zhang, Taoping; Chen, Zhixin; Xie, Lyu; Xu, Ruixian; Chen, Lu; Jia, Ting; Shi, Wengang; Wang, Yongbo; Song, Yuzhu; Han, Qinqin; Xia, Xueshan; Yuan, Tao; et al. (Frontiers in Veterinary Science, 2024)
Japanese encephalitis virus (JEV), a member of the flaviviridae family and a flavivirus, is known to induce acute encephalitis. Vimentin protein has been identified as a potential receptor for JEV, engaging in interactions with the viral membrane protein. The Fc fragment, an integral constituent of immunoglobulins, plays a crucial role in antigen recognition by dendritic cells (DCs) or phagocytes, leading to subsequent antigen presentation, cytotoxicity, or phagocytosis. In this study, we fused the receptor of JEV vimentin with the Fc fragment of IgG and expressed the resulting Vimentin-Fc fusion protein in E. coli. Pull-down experiments demonstrated the binding ability of the Vimentin-Fc fusion protein to JEV virus in vitro. Additionally, we conducted inhibition assays at the cellular level, revealing the ability of Vimentin-Fc protein suppressing JEV replication, it may be a promising passive immunotherapy agent for JEV. These findings pave the way for potential therapeutic strategies against JEV.